Augmented wealth in Switzerland: The influence of pension wealth on wealth inequality - Ursina Kuhn (Swiss Journal of Economics and Statistics, 2020)
Entitlements for social security and occupational pensions present a major wealth component and play a central role for financial security. However, most individual-level data lacks information on pension wealth. By linking various data sources, this contribution estimates the present value of future pension entitlements in Switzerland for statutory pensions, occupational pensions and third pillar accounts and analyses the distribution of augmented wealth, which combines pension wealth and net worth. The CH-SILC survey from 2015 is used to estimate real assets, financial assets and pension wealth of retired individuals. The pension entitlements of non-retired individuals are simulated on the basis of their earning history from administrative records following the accrual method and assuming a real discount rate of 2%. When pension wealth is added to net worth, average wealth doubles, and the Gini-coefficient declines by 26%. The equalising effect is particularly strong for social security pensions. The wealth distribution differs strongly between the three pillars of the pension system; there are also strong differences between gender and age groups. In Switzerland, wealth accumulation continues after retirement age.
Keywords: 330; Net worth; Augmented wealth; Pension wealth; Wealth inequality; Life cycle; SILC; Data linkage